A first constraint on the average mass of ultra-diffuse galaxies from weak gravitational lensing. Issue 3 (11th October 2017) - Sifón, Cristóbal; van der Burg, Remco F. J.; Hoekstra, Henk; Muzzin, Adam; Herbonnet, Ricardo
Abstract: The recent discovery of thousands of ultra-diffuse galaxies (UDGs) in nearby galaxy clusters has opened a new window into the process of galaxy formation and evolution. Several scenarios have been proposed to explain the formation history of UDGs, and their ability to survive in the harsh cluster environments. A key requirement to distinguish between these scenarios is a measurement of their halo masses which, due to their low surface brightnesses, has proven difficult if one relies on stellar tracers of the potential. We exploit weak gravitational lensing, a technique that does not depend on these baryonic tracers, to measure the average subhalo mass of 784 UDGs selected in 18 clusters at z ≤ 0.09. Our sample of UDGs has a median stellar mass 〈 m ⋆ 〉 = 2 × 10 8 M⊙ and a median effective radius 〈 r eff 〉 = 2.8 kpc. We constrain the average mass of subhaloes within 30 kpc to log m UDG ( r < 30 kpc)/M⊙ ≤ 10.99 at 95 per cent credibility, implying an effective virial mass log m 200 /M⊙ ≤ 11.80, and a lower limit on the stellar mass fraction within 10 kpc of 1.0 per cent. Such mass is consistent with a simple extrapolation of the subhalo-to-stellar mass relation of typical satellite galaxies in massive clusters. However, our analysis is not sensitive to scatter about this mean mass; the possibility remains that extreme UDGs reside in haloes as massive as the Milky Way.